Voices of Swiss Paralympic athletes: Perspectives on mental health and well-being - Lucas Lüdi; Georg Pfarrwaller; Christian Imboden; Olivia Stoffel; Matthias Schlüssel; Andreas Heiniger; Birgit Kleim; Nikolai Kiselev (Bern Open Publishing, 2024)
Introduction The aim of this study is to provide an overview of Paralympic athletes' views on mental health in a competitive sport context. Although research in the field of Paralympic sport has increased exponentially over the last two decades, mental health and its promotion have hardly been the subject of research so far (Claussen et al., 2022). Previous research shows that the practice of competitive sports influences the mental health of Paralympic athletes both positively and negatively (Swartz et al., 2019). Mental disorders are no exception, even in elite sports. Well-coordinated health care for the prevention and treatment of mental health challenges and mental disorders in elite sports is crucial for this purpose. Methods The methodological approach of the present study is based on a qualitative research design. The data was collected through semi-structured interviews and their evaluation with the help of applied thematic analysis (Guest et al., 2012). For the interviews, 15 active, adult, Swiss elite Para athletes were recruited. Results The results suggest that athletic success, the athletic activity itself and an improvement in physical health can lead to an increase in mental well-being. On the other hand, athletic failure, pressure to perform, and physical problems can cause psychological stress and facilitate mental disorders. (Lüdi et al., 2023). Conclusion In particular, the coordinated handling of mental health challenges and mental disorders among Paralympic athletes seems to need improvement, especially regarding the use of sports psychiatry and psychotherapy services. References Claussen, M. C., Imboden, C., Raas, M. I., Hemmeter, U., Seifritz, E., & Hofmann, C. G. (2022). Sportpsychiatrie und -psychotherapie im Leistungssport - Interdisziplinäre und interprofessionelle Versorgung und Zusammenarbeit [Sports psychiatry in competitive sports - Interdisciplinary and interprofessional care and collaboration]. Praxis, 111(4), 213-219. https://doi.org/10.1024/1661-8157/a003849 Guest, G., MacQueen, K., & Namey, E. (2012). Applied Thematic Analysis. SAGE. https://doi.org/10.4135/9781483384436 Lüdi, L., Pfarrwaller, G., Imboden, C., Stoffel, O., Schlüssel, M., Heiniger, A., Kleim, B., & Kiselev, N. (2023). Perspectives on mental health and well-being: Voices of Swiss paralympic athletes. Sports Psychiatry: Journal of Sports and Exercise Psychiatry. Advance online publication. https://doi.org/10.1024/2674-0052/a000057 Swartz, L., Hunt, X., Bantjes, J., Hainline, B., & Reardon, C. L. (2019). Mental health symptoms and disorders in Paralympic athletes: A narrative review. British Journal of Sports Medicine, 53(12), 737-740. https://doi.org/10.1136/bjsports-2019-100731